Mechanical properties of different bamboo species - Awalluddin, D.; Mohd Ariffin, M.; Osman, M.; Hussin, M.; Ismail, Mohamed; Lee, H.; Abdul Shukor Lim, N. (2017)
© The Authors, published by EDP Sciences, 2017. Bamboo is a rapid renewable plant that has a fast growth rate as compared to trees, which increases its suitability to be used as a sustainable source for wood industry, especially in construction works. Due to the lack of understanding on bamboo properties, the utilization of bamboo in construction has always been neglected. This paper presents an investigation on the mechanical properties of four species of treated bamboos that are available in Malaysia, which include Bambusa Vulgaris, Dendrocalamus Asper, Schizostachyum Grande, and Gigantochloa Scortechinii. A mechanical testing was carried out in various parts along the culm of these bamboo species in order to examine the differences of their compressive strength and tensile strength. The strength development and moisture content of these bamboo species were also monitored at a five-month interval. The results showed that Bambusa Vulgaris, Dendrocalamus Asper, and Gigantochloa Scortechinii possess excellent mechanical properties in compression and tensile strength, which indicate a good quality to be used as a construction material. As bamboo offers promising advantages, thus, it is suitable to be used as a substitute in place of structural timber in construction, which indirectly facilitates the preservation of the global environment.